E-2-hexenal promotes susceptibility to Pseudomonas syringae by activating jasmonic acid pathways in Arabidopsis - Scala, Alessandra; Mirabella, Rossana; Mugo, Cynthia; Matsui, Kenji; Haring, Michel A.; Schuurink, Robert C. (Frontiers in Plant Science, 2013)
Green Leaf Volatiles (GLVs) are C6-molecules - alcohols, aldehydes and esters - produced by plants upon herbivory or during pathogen infection. Exposure to this blend of volatiles induces defence-related responses in neighboring undamaged plants, thus assigning a role to GLVs in regulating plant defences. Here we compared Arabidopsis thaliana ecotype Ler with a hydroperoxide lyase line, hpl1, unable to synthesize GLVs, for susceptibility to Pseudomonas syringae pv. tomato (DC3000). We found that the growth of DC3000 was significantly reduced in the hpl1 mutant. This phenomenon correlated with lower jasmonic acid (JA) levels and higher salicylic acid (SA) levels in the hpl1 mutant. Furthermore, upon infection, the JA-responsive genes VSP2 and LEC were only slightly or not induced, respectively, in hpl1. This suggests that the reduced growth of DC3000 in hpl1 plants is due to the constraint of JA-dependent responses. Treatment of hpl1 plants with E-2-hexenal, one of the more reactive GLVs, prior to infection with DC3000, resulted in increased growth of DC3000 in hpl1, thus complementing this mutant. Interestingly, the growth of DC3000 also increased in Ler plants treated with E-2-hexenal. This stronger growth was not dependent on the JA-signaling component MYC2, but on ORA59, an integrator of JA and ethylene signaling pathways, and on the production of coronatine by DC3000. GLVs may have multiple effects on plant-pathogen interactions, in this case reducing resistance to P. syringae via JA and ORA59.